Customers' awareness and knowledge level of fraudulent acts in electronic banking in Ghana: evidence from a universal bank. Issue 3 (11th November 2020) - Amoh, John Kwaku; Awunyo-Vitor, Dadson; Ofori-Boateng, Kenneth
Abstract : Purpose: This study aims to assess customers' awareness and level of knowledge on electronic banking fraud. Design/methodology/approach: A well-structured interviewer-assisted questionnaire was used to collect data from 400 clients of a case study bank. Data were analysed using descriptive statistics. Kendall's coefficient of concordance (W) statistic was also estimated to track and rank the fraudulent activities identified by the respondents with respect to electronic banking. Findings: This study found that respondents were aware of most of the specific forms of electronic banking fraud. Firstly, automated teller machinfraud is the most common scam for which customers are aware of. Secondly, institutional factors such as lack of monitoring and education of clients are major factors which expose the bank and clients to fraudulent electronic banking acts. Thirdly, the most effective action that can be taken to prevent fraud in the bank is increased security and personal identification number (PIN) protection education. Research limitations/implications: This study focusses on a universal bank and uses data from customers of only one branch of the bank to achieve the research objectives. Originality/value: One uniqueness of this paper is in the adoption of Kendall's coefficient of concordance (W) statistic to track and rank fraudulent banking activities. The findings will allow financial institutions to know the forms of current and innovative electronic banking fraudulent activities that customers are aware of. It will also enable the banks to find ways to inform their clients about emerging electronic banking fraudulent activities to prevent them from falling victims.